2015
DOI: 10.1016/j.juro.2014.10.100
|View full text |Cite
|
Sign up to set email alerts
|

Equivocal Ureteropelvic Junction Obstruction on Diuretic Renogram—Should Minimally Invasive Pyeloplasty be Offered to Symptomatic Patients?

Abstract: In patients with radiographic equivocal ureteropelvic junction obstruction and flank pain minimally invasive pyeloplasty efficaciously provides symptomatic relief and functional preservation. Results are comparable to those in patients with high grade obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…The estimated reporting of ‘equivocal results’ in most series is 15%. 7-9 In our series, 52% had equivocal T 1/2 which may be attributed to testing at various independent radiological centers outside of our tertiary referral institution. We found a wide range of nonstandard protocols being used at these centers to perform MAG3 renal scans and great divergence in the interpretation of results on radiographic reports.…”
Section: Commentmentioning
confidence: 59%
See 1 more Smart Citation
“…The estimated reporting of ‘equivocal results’ in most series is 15%. 7-9 In our series, 52% had equivocal T 1/2 which may be attributed to testing at various independent radiological centers outside of our tertiary referral institution. We found a wide range of nonstandard protocols being used at these centers to perform MAG3 renal scans and great divergence in the interpretation of results on radiographic reports.…”
Section: Commentmentioning
confidence: 59%
“…A second study from Ozayer et al reported mutual symptom relief in patients after pyeloplasty regardless of any evidence of obstruction on the preoperative renal scan. 7 In our cohort, a relatively high number of patients had a normal T1/2 that ultimately underwent pyeloplasty and achieved symptomatic relief. We confirmed the presence of UPJO with retrograde ureterograms for patients who had a compelling history for UPJO with a normal T 1/2 hprior to pyeloplasty.…”
Section: Commentmentioning
confidence: 82%
“…Percutaneous nephrostomy was first described in 1955 by Goodwin et al for relief of an obstructed kidney and became a widely accepted procedure in children in the 1980s. 9,10,11,12 . Some reports in the 1980s described the use of PCN as an easy and safe procedure to determine the recoverability of renal function in obstructed kidneys (13) with a high technical success rate (88-99%) and a low complication rate (4-8%) (14,15) .…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional abdominal imaging at the time of acute pain is critical for identifying hydronephrosis. While a renal scan is the gold standard to document functional obstruction, a recent study by Ozayar et al noted that almost all patients with a highly suggestive clinical picture but equivocal renal scan findings benefit from surgical correction [ 5 ]. In this case, the classic clinical history and definitive CT findings at the time of pain obviated the need for a renal scan.…”
Section: Discussionmentioning
confidence: 99%